ANALISIS PARAMETER KONDISI OPERASI PROSES PASTUERISASI TERHADAP KUALITAS PRODUK MINUMAN KEMASAN - MUH FIQRI; A. Sry Iryani; Mansyur, Andi Irsyam (UIR Press, 2026)
This study aims to analyze the effect of pasteurization process operating parameters—including temperature, contact time, flow rate, and pH—on the quality of packaged beverages, particularly flavored beverages and tea drinks. The pasteurization process is a thermal processing method used in the beverage industry to improve microbiological safety and extend product shelf life. The success of this process is highly influenced by the combination of operating parameters used. The research was conducted experimentally by varying the temperature, contact time, and flow rate during the pasteurization process, followed by product quality testing that included chemical parameters (pH and °Brix), microbiological parameters (total plate count/TPC), and organoleptic parameters (hedonic test). The data were analyzed descriptively to examine the relationship between process parameters and product quality. Based on the research results, it can be concluded that the appropriate combination of pasteurization parameters significantly determines the final product quality, both from chemical, microbiological, and organoleptic aspects. The results indicate that for flavored beverages, pasteurization at 65°C with sufficient contact time and a balanced flow rate effectively reduces microbial counts to undetectable levels while maintaining organoleptic quality. Meanwhile, for tea beverages, conditions at 135°C yield the best results in terms of microbiological safety and consumer acceptability. Excessively high temperatures lead to a decline in sensory quality due to the degradation of flavor and aroma components.